Contextualising regional policy for territorial cohesion in Central and Eastern Europe - Loewen, Bradley (Hungarian Geographical Bulletin, 2015)
This conceptual paper discusses key instruments for territorial cohesion in Central and Eastern Europe (CEE) from a comparative historical analytical perspective amidst the neoliberalisation of EU Regional Policy, which has implications for the production and reinforcement of spatial inequalities in regional development. The neoliberalisation processes unfolding in the diff erent political-institutional contexts of CEE have implications for the movement, transformation and effectiveness of policies such as Regional Policy, complicating the holistic understanding of policy effects. Increasingly neoliberal regional policies across Europe, and in the different path dependent political-institutional contexts of CEE in particular, raise questions about the effectiveness of Regional Policy to achieve territorial cohesion. Comparative historical analysis provides a method of inquiry into path dependent processes shaping institutions and affecting policy outcomes, and is therefore a useful approach for conceptualising regional political-institutional contexts and their implications for Regional Policy. Operational Programmes encompassed in national strategic documents from the Czech Republic, Estonia and Hungary over three programming periods are examined as the key instruments for the implementation of Regional Policy, the comparison of which reveals a diff erence in perspectives towards the common EU goals of competitiveness and growth as a means of achieving territorial cohesion. The research thus points to the need for deeper comparative understanding of the political-institutional contexts in the three countries in order to identify factors of effective policies and to tailor effective policy solutions to specific regional contexts, a task to be advanced in future studies of Regional Policy and political institutional contexts of CEE.